Mauqif Ibn Taimiyah Min al-Asy`ariy fī Qaḍiyyah al-Īmān - Rif’at Husnul Ma’afi; Joko Kurniawan (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2020)
Islam and faith are two important elements of religion. Disputes in the issue of faith have taken place among the scholars who discuss the existence and polemics in it. Among the well-known scholars of the Ahlussunnah wa al-Jama'ah, namely Abu Al-Hasan Asy'ari, argued that faith is a justification made in the heart and expressed verbally. However, most scholars disputed Asy'ari's statement about faith, one of which was Syaikhulal-Islam Ibn Taimiyah who said that faith is not enough with heart justification and verbal speech but must be accompanied by the charity as an idea of justification. With the differences of opinion between both of them. this article seeks to identify Ibn Taimiyah's attitude or view of Imam Asy'ari in matters of faith. Through the kalamiyah approach that uses descriptive methods and analysis of a number of findings are produced. That, Ibn Taimiyah denied al-Asy'ari's statement which referred to linguists as the basis of the concept of faith and did not rely on the arguments of the Qur'an and Sunnah. This is because the Sanad is not known for the statement if the understanding of faith is just then it is a depiction of Ahad and is not determined based on mutilated recitation, because there is no mention of an amplifier from the words of the Arabs. Whereas the mistake mentioned by Ibn Taymiyyah in the concept of faith al-Ash'ari, actually does not come out of the view of the Salaf scholars, namely that faith is justification in the heart and knows it, but that al-Asy'ari holds that charity in the concept of faith is something the external concept of faith itself. In addition, Ibn Taimiyah also contends with Asy'ari that faith decreases and increases decreases due to disobedience and increase because of remembering Allah and His Messenger.